The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1111/1365-2435.12439
|View full text |Cite
|
Sign up to set email alerts
|

Active prey mixing as an explanation for polyphagy in predatory arthropods: synergistic dietary effects on egg production despite a behavioural cost

Abstract: Summary Mixing of prey that differ in nutrient content or toxic compounds (dietary mixing) may allow synovigenic predatory arthropods to balance their diet or dilute toxins of different prey items to maximize performance: dietary mixing may therefore explain the prevalence of polyphagy in this functional group. Several predatory arthropods can redress nutritional imbalances in their diet by actively mixing different diets, based on experiments with artificial diets or with prey that were manipulated to conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 59 publications
2
35
1
Order By: Relevance
“…Since then, it has become clear that many more factors are involved in patch selection by predators, such as the need for a mixed diet (Belovsky 1978; Mayntz et al 2005; Marques et al 2015) and the avoidance of competing species (Janssen et al 1995; Adler et al 2001) and of intraguild predators (Moran and Hurd 1994; Magalhães et al 2005; Choh et al 2010). Also, when different prey species co-occur on the same patch, the interactions between these prey can affect patch quality and patch selection for predators (Werner and Peacor 2003; Ohgushi 2005; Schmitz et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, it has become clear that many more factors are involved in patch selection by predators, such as the need for a mixed diet (Belovsky 1978; Mayntz et al 2005; Marques et al 2015) and the avoidance of competing species (Janssen et al 1995; Adler et al 2001) and of intraguild predators (Moran and Hurd 1994; Magalhães et al 2005; Choh et al 2010). Also, when different prey species co-occur on the same patch, the interactions between these prey can affect patch quality and patch selection for predators (Werner and Peacor 2003; Ohgushi 2005; Schmitz et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hilbeck et al (1998a) reported that the generalist predator C. carnea experienced reduced larval survival and longer development time when fed a diet of European corn borer (ECB), Ostrinia nubilalis (Hübner) (Lepidoptera: Crambidae), that had consumed Bt corn. However, generalist predators are capable of preferential feeding on healthy prey (Ferry et al, 2006) and are able to shift their dietary preferences to consume the mixture of nutrients required for optimal fitness (Mayntz et al, 2005; Raubenheimer et al, 2007; Marques et al, 2015). Therefore, generalist predators may be able to compensate for reduced quality of select prey due to Bt toxin consumption, having a negligible impact on biological control.…”
Section: Genetically Modified Crops and Interactions With Biological mentioning
confidence: 99%
“…Although this disruption does not seem to occur very often, it does in some systems (Janssen et al., ; Rosenheim & Harmon, ). We therefore investigated the occurrence of IGP and reciprocal IGP between two predatory mite species that are considered for biological control of pests of the biodiesel plant Jatropha curcas L., on which both species occur (Marques et al., ; Sarmento et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…We therefore investigated the occurrence of IGP and reciprocal IGP between two predatory mite species that are considered for biological control of pests of the biodiesel plant Jatropha curcas L., on which both species occur (Marques et al, 2015;Sarmento et al, 2011).…”
mentioning
confidence: 99%